Public Policy Implementation with Systemic Thinking for Sustainable Development - Sucha, Naravit; Pulteabrat, Prawit; Phuekjantuek, Trenapa; Parisutthipricha, Khanathip; Deegade, Nuttapol; Rojanatrakul, Tanastha (Journal of Graduate MCU KhonKaen Campus, 2025)
Public policy implementation process required systematic thinking and learning throughout the cycle, giving importance to current issues and situations in order to have complete and relevant information and knowledge as an alternative for systematic problem solving, and be able to define and explain the scope of issues, mechanisms, processes, and stakeholders involved. Therefore, the public policy implementation with systematic thinking for sustainable development required an understanding of the problem owners, which were humans, as well as the environment or context that affected feelings and thoughts in order to reflect the problems through 8 processes: 1) Explore policy issues, 2) Create a whole problem map, 3) Develop system goals, 4) Review system dynamics, 5) Brainstorm and develop proposals, 6) Evaluate and test policy proposals, 7) Plan and implement policies, and 8) Monitor and evaluate policies.